Anticancer Drug 2-Methoxyestradiol Protects against Renal Ischemia/Reperfusion Injury by Reducing Inflammatory Cytokines Expression. (25th August 2014) - Chen, Ying-Yin; Yeh, Ching-Hua; So, Edmund Cheung; Sun, Ding-Ping; Wang, Li-Yun; Hsing, Chung-Hsi
Abstract : Background . Ischemia/reperfusion (I/R) injury is a major cause of acute renal failure and allograft dysfunction in kidney transplantation. ROS/inflammatory cytokines are involved in I/R injury. 2-Methoxyestradiol (2ME2), an endogenous metabolite of estradiol, inhibits inflammatory cytokine expression and is an antiangiogenic and antitumor agent. We investigated the inhibitory effect of 2ME2 on renal I/R injury and possible molecular actions. Methods . BALB/c mice were intraperitoneally injected with 2ME2 (10 or 20 mg/kg) or vehicle 12 h before and immediately after renal I/R experiments. The kidney weight, renal function, tubular damages, and apoptotic response were examined 24 h after I/R injury. The expression of mRNA of interleukin-1 β, tumor necrosis factor- (TNF) α, caspase-3, hypoxia inducible factor- (HIF) 1 α, and proapoptotic Bcl-2/adenovirus E1B 19 kDa interacting protein 3 (BNIP3) in kidney tissue was determined using RT-PCR, while the expression of nuclear factor κ B (NF- κ B), BCL-2, and BCL-xL, activated caspase-9, and HIF-1 α was determined using immunoblotting. In vitro, we determined the effect of 2ME2 on reactive oxygen species (ROS) production and cell viability in antimycin-A-treated renal mesangial (RMC) and tubular (NRK52E) cells. Results . Serum creatinine and blood urea nitrogen were significantly higher in mice with renal I/R injury than in sham control and in I/R+2ME2-treated mice. Survival in I/R+2ME2-treated mice was higher than in I/R mice. Histological examination showed that 2ME2 attenuated tubular damage in I/R mice, which was associated with lower expression TNF- α, IL-1 β, caspase-9, HIF-1 α, and BNIP3 mRNA in kidney tissue. Western blotting showed that 2ME2 treatment substantially decreased the expression of activated caspase-9, NF- κ B, and HIF-1 α but increased the antiapoptotic proteins BCL-2 and BCL-xL in kidney of I/R injury. In vitro, 2MR2 decreased ROS production and increased cell viability in antimycin-A-treated RMC and NRK52E cells. Conclusions . 2ME2 reduces renal I/R injury in mice because it inhibits the expression of ROS and proinflammatory cytokines and induces antiapoptotic proteins.